The Application of and Factors Influencing, the NB5 Assay in Neuroblastomas - Wang, Zuopeng; Wang, Chengyun; Xu, Yibing; Le, Jun; Jiang, Yuan; Yao, Wei; Wang, Hongsheng; Li, Kai (Frontiers in Oncology, 2021)
Purpose: The NB5 assay was performed in bone marrow(BM) and peripheral blood(PB) to detect neuroblastomas(NB) with micrometastases. The sensitivity and factors influencing the NB5 assay were preliminarily evaluated. Methods: The NB5 assay uses RT-PCR to detect the co-expression of five mRNAs from the neuroblastoma-associated genes, CHGA, DCX, DDC, PHOX2B, and TH. We enrolled 180 cases of neuroblastoma and 65 cases of non-neuroblastoma. Bone marrow and peripheral blood were collected from every patient. The gold standard for the diagnosis of NB was pathological evaluation of solid tumor specimens or bone marrow biopsies(BMB) from hematological tumors. STATA version 15 and SPSS version 17 software were used for analysis. Results: We found that 17 patients were BMB(+) and they were diagnosed as the International Neuroblastoma Staging System (INSS) stage IV, and the high-risk group. All 17 patients were BM(+), while 15 patients were PB(+) (15/17, 88.2%). Among the 163 children who were BMB(-), 56 were BM(+), 40 were PB(+), and 36 were BM(+) and PB(+). The sensitivity of the NB5 assay in BM(40.5%) and PB(30.5%) was significantly higher than the sensitivity of BMB(9.4%, P = 0.000). In the non-NB group, four cases were BM(+) and one case was PB(+). The specificity of the NB5 assay in BM and PB was 93.8% and 98.5%, respectively. The sensitivity of the NB5 assay in both BM and PB in INSS stage IV patients was significantly higher than that in INSS stage I-II patients(P < 0.05). The sensitivity of the NB5 assay in both BM and PB in the high risk group was significantly higher than that in the middle-low-risk groups(P = 0.0001). Logistic regression analyses indicated that liver metastases and bone metastases were the primary factors influencing the sensitivity of the NB5 assay in BM and PB(P < 0.05). Conclusions: The NB5 assay had significantly higher sensitivity than the pathological analysis of BMB in detecting NB with micrometastases. The NB5 assay had higher sensitivity in INSS stage IV or the high-risk group. Liver metastases and bone metastases were the primary factors that affected the sensitivity of the NB5 assay.